2000
DOI: 10.1001/archneur.57.9.1363
|View full text |Cite
|
Sign up to set email alerts
|

Hemiplegic Migraine Induced by Exertion

Abstract: Migraine aura should be included in the differential diagnosis of exertion-induced focal neurologic deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…1 However, patients with similar clinical symptoms but without other affected family members have been reported, 2-13 and the term sporadic hemiplegic migraine (SHM) has been used. 2,7,9,11,12 Currently, these patients are classified as having migraine with typical aura (MA) or migraine with prolonged aura according to the classification of the International Headache Society (IHS classification).We examined the similarity of the clinical characteristics of SHM to those of MA and those of FHM by comparing SHM with our data on FHM 14 and with a historical group of patients with MA. 15 Materials and methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, patients with similar clinical symptoms but without other affected family members have been reported, 2-13 and the term sporadic hemiplegic migraine (SHM) has been used. 2,7,9,11,12 Currently, these patients are classified as having migraine with typical aura (MA) or migraine with prolonged aura according to the classification of the International Headache Society (IHS classification).We examined the similarity of the clinical characteristics of SHM to those of MA and those of FHM by comparing SHM with our data on FHM 14 and with a historical group of patients with MA. 15 Materials and methods.…”
mentioning
confidence: 99%
“…1 However, patients with similar clinical symptoms but without other affected family members have been reported, [2][3][4][5][6][7][8][9][10][11][12][13] and the term sporadic hemiplegic migraine (SHM) has been used. 2,7,9,11,12 Currently, these patients are classified as having migraine with typical aura (MA) or migraine with prolonged aura according to the classification of the International Headache Society (IHS classification).…”
mentioning
confidence: 99%
“…There are anecdotal reports of episodes of migraine preceded by head trauma and visual symptoms (with a past history of non-sports-related migraine) [6], migraine prodrome symptoms after unusually strenuous running with no subsequent head pain [7] or recurrent attacks of hemiplegic migraine induced only by exertion [8]. …”
Section: Discussionmentioning
confidence: 99%
“…In our patients, exertion seems to precipitate the aura. It has been suggested that the combination of exertion-induced hyperventilation and the subsequent hypocapnia with respiratory alkalosis and hypomagnesemia predisposes these patients to cerebral vasoconstriction during exertion lowering the threshold for the development of CSD or aura in migraineurs [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Four patients with SHM were administered 120 mg verapamil orally from once to three times daily and experienced a significant reduction of attack frequency 81,104 . Furthermore, a female with exertion‐induced SHM enjoyed remission taking verapamil 105 . Following these reports, I used verapamil in several FHM/SHM patients without marked efficacy (A. Ducros, personal data).…”
Section: Preventive Agentsmentioning
confidence: 99%